DNA vaccine encoding Middle East respiratory syndrome coronavirus S1 protein induces protective immune responses in mice. Issue 16 (11th April 2017) - Chi, Hang; Zheng, Xuexing; Wang, Xiwen; Wang, Chong; Wang, Hualei; Gai, Weiwei; Perlman, Stanley; Yang, Songtao; Zhao, Jincun; Xia, Xianzhu
Highlights: DNA vaccine encoding MERS-CoV S1 gene induced humoral and cellular immune responses. High titers of neutralizing antibodies were generated without adjuvant. Virus loads in lungs significantly decreased in vaccinated and serum received mice. Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV), is an emerging pathogen that continues to cause outbreaks in the Arabian peninsula and in travelers from this region, raising the concern that a global pandemic could occur. Here, we show that a DNA vaccine encoding the first 725 amino acids (S1) of MERS-CoV spike (S) protein induces antigen-specific humoral and cellular immune responses in mice. With three immunizations, high titers of neutralizing antibodies (up to 1: 10 4 ) were generated without adjuvant. DNA vaccination with the MERS-CoV S1 gene markedly increased the frequencies of antigen-specific CD4 + and CD8 + T cells secreting IFN-γ and other cytokines. Both pcDNA3.1-S1 DNA vaccine immunization and passive transfer of immune serum from pcDNA3.1-S1 vaccinated mice protected Ad5-hDPP4-transduced mice from MERS-CoV challenge. These results demonstrate that a DNA vaccine encoding MERS-CoV S1 protein induces strong protective immune responses against MERS-CoV infection.